Not just at school: Inclusion of children with autism spectrum disorder in a weight management program in a community pediatric setting. (April 2021) - Espinoza, Juan C; Deavenport-Saman, Alexis; Solomon, Olga; Chowdhuri, Sampreeti; Wee, Choo Phei; Azen, Collen; Orozco, Jazminne; Kreutzer, Cary; Yin, Larry
Children with autism spectrum disorder are at increased risk for obesity compared to typically developing children. Many obesity intervention programs exclude children with autism spectrum disorder. There is little research on developmentally inclusive approaches to pediatric weight management. We examined the outcomes of children and families with autism spectrum disorder in an inclusive, comprehensive behavioral family-based lifestyle intervention. A secondary analysis of a randomized controlled trial on families enrolled in a comprehensive behavioral family-based lifestyle intervention was conducted. Analyses included chi-square or Fisher's exact tests to examine family and child differences in program completion rates and multivariate regression analysis using generalized estimating equation to further examine differences in weight outcomes between children with autism spectrum disorder versus no autism spectrum disorder accounting for other covariates. There were 158 families; 15 families had children with autism spectrum disorder. There were no significant differences in demographics, program completion, or weight outcomes between the two groups. Children who completed the intervention had a significant decrease in body mass index Z -scores, but no change in their percentage of the 95th percentiles. Families of children with autism spectrum disorder participated in a comprehensive behavioral family-based lifestyle intervention alongside children without autism spectrum disorder with similar outcomes. Comprehensive behavioral family-based lifestyle intervention can meet the weight management needs of children with autism spectrum disorder using an inclusive approach, expanding access to needed obesity interventions. Lay abstract: Children diagnosed with autism are likely to be more overweight than children who do not have autism. There are many group programs that help children to be more physically active and improve their eating habits to achieve healthy weight, but most of these programs do not allow children with autism to participate. We studied a program that was specially adapted so children with autism could participate together with peers who do not have autism. The program lasted 8 weeks and was offered in the evening at a large healthcare center in a big city. The children participated with a parent or another adult who takes care of them. We analyzed data that were part of a previous project where we studied how physical activity trackers called Fitbit help overweight children to change their eating and exercise habits so they can achieve healthier weight. Out of 158 families in the study, 15 families had a child or children with autism. We measured changes in the weight of children with and without autism and compared how many of the children completed the program. Children who had autism had similar results in achieving healthy weight and finishing the program compared to their peers without autism. Our study found that when a group weight management program is slightly changed to meet the needs of children with autism, they can successfully participate and benefit similarly to their peers who do not have autism. Registration: This trial was registered with ClinicalTrials.gov (NCT03215641).